Intonation in a glossolalic corpus: Biological and communicative factors - De Dominicis, Amedeo (Association for Scientific Computing Electrical and Engineering (ASCEE), 2025)
This study investigates the suprasegmental properties of glossolalic speech, particularly focusing on intonation patterns observed in a corpus (15 recordings) of glossolalic prayers recorded by 11 native German speakers. Glossolalia, often interpreted as divinely inspired speech, lacks semantic content but exhibits structured phonetic features. An earlier analysis conducted by the corpus owners revealed that glossolalic syllables, although meaningless, follow frequency patterns similar to those of the speakers’ native language. The present study analyzes intonation using the Prosogram script available in Praat, and the results show that the melodic contours primarily follow a falling–falling pattern within breath groups, suggesting a physiological, rather than communicative, origin. This downward F0 trend is interpreted through the lens of Gussenhoven’s biological codes, emphasizing the dominance and finality encoded in such patterns. The corpus was recorded in semi-spontaneous conditions, which is particularly rare in the case of glossolalic speech. The approach adopted in the paper is innovative: it uses a spectrographic and intonation analysis but combines the results with a pragmatic investigation on the communicative intentions of the speakers. Glossolalia is interpreted not as a prayer, but as the imitation of a non-human, divine language.